Aspek Hukum Terhadap Wanprestasi Dalam Perjanjian Sewa Menyewa Menurut Kitab Undang-Undang Hukum Perdata - Mahalia Nola Pohan; Sri Hidayani (Universitas Harapan Medan, 2020)
Renting is an agreement with which one party binds itself to give to the other party to using of an item for a certain time and with a payment of a price which latter the party is able to pay. The rights and obligations of the parties on leasing agreement, the rights of the party that rents out are the rights to be received by the party who rents out. The leasing party has the right to rent which must be paid by the lessee at a certain time in accordance with the lease agreement. The renting party has the right to pandbeslag, which is the seizure carried out by the court on leasing applications such as furniture that is at home rented in the event that the tenant is in arrears of rent for auction if the tenant does not pay the arrears in full. The leasing party has the right to request the cancellation of the agreement and compensation. The right of the lessor is to give back the object that is leased to the tenant, maintaining the object that is leased so that it can be used for the intended purpose. The lease agreement ends with breach of contract before the expiry of the lease agreement can expire on its own at a certain time, after being stopped with due regard to a certain grace period. Even though a lease is a consensual agreement, but by law there is a difference between a written rental and an oral lease.